CAR-T cell therapy for juvenile-onset autoimmune diseases: a promising future? - Maurine Jouret; Sebastien Viel; Benjamin Fournier; Sarah Benezech; Jérome Avouac; Marc Scherlinger; Alexandre Belot; for the C3I consortium (Arthritis Research & Therapy)
Abstract Chimeric antigen receptor (CAR) T-cell therapy targeting B cells has shown promising results, including drug-free remission, in adult-onset autoimmune diseases. Extending this therapeutic approach to the pediatric population, particularly for juvenile autoimmune diseases, presents an exciting opportunity. However, challenges specific to juvenile-onset autoimmune conditions, such as long-term adverse events, heightened disease activity, and the imperative to reduce steroid exposure, must be considered. While this strategy appears viable for these severe conditions, the limited data available for this population and the absence of evidence on cases with a high genetic component, such as monogenic lupus, represent significant challenges. Most monogenic lupus cases are associated with innate immune defects, and the involvement of B cells in these genetic anomalies remains poorly understood. In this review, we examine the potential indications, current knowledge, and limitations of CAR-T cell therapy in juvenile-onset autoimmune diseases, extending the discussion beyond early-onset lupus.